Deamination of Betti bases: a facile route to 1-alkyl-2-naphthols and phenols via a metal-free transfer hydrogenation under microwave irradiation. Issue 27 (1st July 2015) - Dutta, Prantu; Pegu, Choitanya Dev; Deb, Mohit L.; Baruah, Pranjal K.
Graphical abstract: Abstract: A facile route to 1-alkyl-2-naphthols/phenols via deamination followed by a metal-free catalytic transfer hydrogenation of 1-(α-aminoalkyl)-2-naphthols/phenols, commonly called Betti bases under microwave irradiation has been developed. Hantzsch 1, 4-dihydropyridine is used as the reductant. A mechanistic proposal involving elimination–addition mechanism is described. The reaction is simple, clean, and offers very good yields of products.